SAT0260 Biomarkers Associated with Rheumatoid Arthritis Disease Activity Including Joint Damage Correlate with Changes in Clinical Response in Subjects Treated with Mavrilimumab at Doses above 10 Mg. (10th June 2014) - White, W.; Ryan, P.C.; Guo, X.; Sinibaldi, D.; Ranganna, G.; Godwood, A.; Saurigny, D.; Close, D.; Eck, S.; Wilkins, D.; Roskos, L.; Sleeman, M.; et al.
Abstract : Background: Mavrilimumab is a human monoclonal antibody targeting the alpha subunit of GM-CSF receptor and was recently evaluated in RA subjects in a phase 2a study (EARTH). Results reported from the European (EU) cohort demonstrated that mavrilimumab shows activity in subjects with moderate to severe RA (Burmester et al. 2013). Here, we describe final data from EARTH comparing results in the EU and Japanese (JA) cohorts. Objectives: Biomarker (BM) assessments were performed to elucidate mechanistic aspects of mavrilimumab. Methods: Mavrilimumab (10, 30, 50 or 100 mg) or placebo was administered SC every other week to subjects with moderate/severe RA (DAS28 >3.2) on stable methotrexate for 12 weeks followed by a 12 week drug free follow up period. A multi-biomarker disease activity (MBDA) score was calculated using the validated Vectra ®DA algorithm and used to track the effect of the drug on disease activity over time. An additional multi-BM-based algorithm (MBSD) was used to assess the impact of mavrilimumab on markers known to be associated with progressive joint damage. The relative ability of different mavrilimumab doses, over time, to saturate GM-CSF receptors in whole blood was examined by flow cytometry using receptor occupancy assay (ROA) in the EU cohorts. Results: In the EARTH study, the primary endpoint (DAS28-CRP reduction ≥1.2 at Week 12) was met. Improvements were seen as early as week 2 and persisted through the 12 week follow up. The MBDA score decreased significantly as early as day 8 (p<0.05) and remained suppressed during the entire treatment period. Additional samples from the 100 mg EU cohort showed that suppression of the MBDA was maintained for a minimum of 4 weeks after the last dose. Individual components of the MBDA score, as well as additional BMs in the EU cohort showed that CRP, SAA, IL-6, IL-2RA and MDC were significantly decreased on days 8, 15, 88 and 113 in the 100 mg cohort compared to placebo. Lesser or no changes were observed with the 10 mg cohort. There was an early and sustained dose-related inhibition of the joint damage composite index MBSD observed in the EU cohort. In the JA cohort a significant decrease was also observed when comparing treatment group to placebo group. The ROA results showed the 10 mg dose was sub-optimal in its ability to saturate GM-CSF receptor. This sub-optimal effect was reflected in the BM analysis and in the clinical efficacy endpoints. Conclusions: Promising results of mavrilimumab support further clinical development at doses greater than 10 mg. Mechanistically, the drug suppressed both acute phase and inflammatory blood markers. Tracking of disease activity by MBDA showed a clear biomarker-based dose-response relationship. The association of MBSD decline with radiographic damage will be assessed in an on-going phase 2b study. References: Burmester GR, et al. 2013, ARD, 72 (9):1445-52. Disclosure of Interest: W. White Shareholder of: AstraZeneca, Employee of: MedImmune, P. Ryan Shareholder of: AstraZeneca, Employee of: MedImmune, X. Guo Shareholder of: AstraZeneca, Employee of: MedImmune, D. Sinibaldi Shareholder of: AstraZeneca, Employee of: MedImmune, G. Ranganna Shareholder of: AstraZeneca, Employee of: MedImmune, A. Godwood Shareholder of: AstraZeneca, Employee of: MedImmune, D. Saurigny Shareholder of: AstraZeneca, Employee of: MedImmune, D. Close Shareholder of: AstraZeneca, Employee of: MedImmune, S. Eck Shareholder of: AstraZeneca, Employee of: MedImmune, D. Wilkins Shareholder of: AstraZeneca, Employee of: MedImmune, L. Roskos Shareholder of: AstraZeneca, Employee of: MedImmune, M. Sleeman Shareholder of: AstraZeneca, Employee of: MedImmune, W. Li Shareholder of: Crescendo Bioscience, Employee of: Crescendo Bioscience, G. Cavet Shareholder of: Crescendo Bioscience, Employee of: Crescendo Bioscience, N. Defranoux Shareholder of: Crescendo Bioscience, Employee of: Crescendo Bioscience DOI: 10.1136/annrheumdis-2014-eular.5731